381 Repeated Opening of the Blood-Brain Barrier With the Skull-implantable SonoCloud-9 (SC9) Device: Phase 1 Trial of Nab-Paclitaxel and SC9 in Recurrent Glioblastoma. (April 2023) - Sonabend, Adam M.; Gould, Andrew; Luan, Yu; Hou, Ye; Chen, Le; Kobayashi, Mikoto; Castro, Brandyn; Zhang, Daniel; Korobova, Farida; Amidei, Christina; Youngblood, Mark William; Bebawy, John Patrick; et al.
Abstract : INTRODUCTION: The blood-brain barrier (BBB) is a major impediment to pharmacological treatment of gliomas, as these infiltrate the brain. Low-intensity pulsed ultrasound with concomitant intravenous microbubbles (LIPU/MB), opens the BBB. METHODS: To perform LIPU/MB-based BBB opening prior to ABX infusions, we used a novel 6 x 6 cm device with 9 ultrasound emitters (SC9) that is implanted in a skull window after tumor resection. A Phase 1 dose-escalation trial using Bayesian adaptive design was initiated at our institution (NCT04528680). Patients with recurrent operable glioblastoma, a WHO PS ≤ 2 and normal bone marrow and organ function were eligible. After tumor resection and implantation of SC9, repeated cycles of BBB opening by LIPU/MB immediately followed by ABX, were performed Q3W. Intraoperative LIPU/MB and low dose ABX was given prior to tumor resection for pharmacokinetic studies. RESULTS: Seventeen patients were enrolled, and dose levels 40-260 mg/m2 were investigated. At dose of 260 mgm2, a grade 3 reversible taxane-associated encephalopathy was observed in one patient, considered a dose-limiting toxicity. The patient continued treatment at a lower dose in subsequent cycles. A second patient exhibited encephalopathy on cycle 2. Pharmacokinetic studies showed that ABX tissue concentrations in non-enhancing peri-tumoral brain were increased 3.7-fold after LIPU/MB. sc-RNA-sequencing showed transcriptional dysregulation of membrane transporters, pathways related to trans-cytosis as well as cell-cell and cell-matrix adhesion. Ultrastructural analysis of brain capillaries revealed that LIPU/MB led to time-dependent emergence of vesicles in endothelial cells CONCLUSIONS: The LIPU/MB using skull-implantable ultrasound enhances the penetration of ABX in large regions of the brain, a procedure that can be performed repeatedly and safely. LIPU-based BBB opening leads to ultrastructural transcriptional alterations in brain endothelium. Funding: NIH/NCI 1R01CA245969-01A1, CarThera (SC9 devices), BMS/Celgene (Abraxane®).